2017
DOI: 10.1128/aac.00091-17
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Nonantibiotic Nitroglycerin-Based Catheter Lock Solution for Prevention of Intraluminal Central Venous Catheter Infections in Cancer Patients

Abstract: For long-term central lines (CL), the lumen is the major source of central line-associated bloodstream infections (CLABSI). The current standard of care for maintaining catheter patency includes flushing the CL with saline or heparin. Neither agent has any antimicrobial activity. Furthermore, heparin may enhance staphylococcal biofilm formation. We evaluated the safety and efficacy of a novel nonantibiotic catheter lock solution for the prevention of CLABSI. Between November 2015 and February 2016, we enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
0
15
0
10
Order By: Relevance
“…In a previous clinical catheter salvage study, MEE was 100% clinically effective in salvaging central lines for cancer patients with bacterial CLABSIs (6). In vitro studies showed this combination to be synergistically effective against other Candida species (12).…”
mentioning
confidence: 91%
“…In a previous clinical catheter salvage study, MEE was 100% clinically effective in salvaging central lines for cancer patients with bacterial CLABSIs (6). In vitro studies showed this combination to be synergistically effective against other Candida species (12).…”
mentioning
confidence: 91%
“…PAD lock solution is free of antibiotics, and the mechanism of action does not involve specific binding sites on bacteria or fungi, thereby minimizing the risk of selecting for antimicrobial resistance (11). In this context, it is interesting that a 2-h exposure to a non-antibiotic-containing, nitroglycerin-based lock solution reduces bacterial and fungal intraluminal biofilms by 4 orders of magnitude (30,31). Nitroglycerin produces reactive oxygen and nitrogen species (32), and this may explain why its activity against bacteria and fungi is of similarly broad spectrum to PAD.…”
Section: Discussionmentioning
confidence: 99%
“…PAD lock solution is free of antibiotics and the mechanism of action does not involve specific binding sites on bacteria or fungi, thereby minimizing the risk of selecting for antimicrobial resistance (11). In this context, it is of interest to note that a 2 hour exposure to a non-antibiotic containing, nitroglycerin-based lock solution reduces bacteria and fungal intraluminal biofilms by 4 orders of magnitude (19,34). Nitroglycerin produces reactive oxygen and nitrogen species (35) and this may explain why its activity against bacteria and fungi is similarly broad spectrum to PAD.…”
Section: Discussionmentioning
confidence: 99%